2018
DOI: 10.1111/pcmr.12708
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic signaling in uveal melanoma

Abstract: Uveal melanoma is the most common primary cancer of the eye, and despite rapidly emerging insights into the molecular profile of this disease, prognosis of patients with metastatic uveal melanoma remains poor with mortality rates unchanged in over 35 years. Early genetic events activate G protein-coupled receptor signaling in nearly all uveal tumors via mutually exclusive mutations in the GNAQ, GNA11, CYSLTR2, or PLCB4 genes. A multitude of signaling cascades downstream of G protein activation, including prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 123 publications
(143 reference statements)
1
53
0
Order By: Relevance
“…Regarding the genetic results, different genomic alterations, such as chromosome 3 monosomy and gains of chromosome 8q, are predictive of relapse after primary treatment [ 24 28 ]. In this study, we analysed the association between these genomic alterations with PFS.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the genetic results, different genomic alterations, such as chromosome 3 monosomy and gains of chromosome 8q, are predictive of relapse after primary treatment [ 24 28 ]. In this study, we analysed the association between these genomic alterations with PFS.…”
Section: Discussionmentioning
confidence: 99%
“…GLDC (glycine decarboxylase) was recently described as a critical enzyme of tumor‐initiating cells and thus, as a driver of tumorigenesis in lung nonsmall cell cancer . Furthermore, CYSLTR2 , cysteinyl leukotriene receptor 2, has been related to uveal melanoma progression . The upregulation of SULT1C4 would seem fundamental in maintaining establishment primary renal cell lines ccRCC .…”
Section: Discussionmentioning
confidence: 99%
“…Different studies have found a number of mutational signatures in these tumours, most notably one associated with ageing and explained by spontaneous deamination of 5-methylcytosine, and others related to defects in nucleotide excision and in DNA mismatch repair [4,48]. There are currently no known drugs that target GNAQ/GNA11 and alternative pathway inhibitors have so far not shown clinical benefit in early phase trials, reviewed in [110]. A number of trials are ongoing, targeting a range of UM signalling cascades [111].…”
Section: Um: a Sparsely Mutated Melanoma Subtype With Poor Responses mentioning
confidence: 99%